Bee species authentication of commercial honey in Indonesia using the mrjp2 gene - I MADE BUDIARSA; MANAP TRIANTO; I NENGAH KUNDERA (Society for Indonesian Biodiversity, 2026)
Abstract. Budiarsa IM, Trianto M, Kundera IN. 2026. Bee species authentication of commercial honey in Indonesia using the mrjp2 gene. Biodiversitas 27 (4): d270432. https://doi.org/10.13057/biodiv/d270432. Authenticating the entomological origin of honey is essential to ensure product traceability, labeling accuracy, and the conservation of native honey bee species in Indonesia. This study aimed to authenticate the bee species origin of honey marketed in Indonesia using the major royal jelly protein 2 (mrjp2) gene as a molecular marker. A total of 21 honey samples, labeled as forest honey or specific bee-derived honey, were collected from Sulawesi, Sumatra, Kalimantan, Bali, Java, and Yogyakarta. Genomic DNA was extracted and amplified by PCR using two primer pairs targeting the mrjp2 gene (MF-MR and CF-CR). PCR products were sequenced, and the resulting sequences were analyzed using BLAST-N against GenBank references and further evaluated through Maximum Likelihood phylogenetic analysis. The MF-MR primers generated amplicons of approximately 584-593 bp, while CF-CR primers produced fragments of 202-210 bp, consistent with the targeted mrjp2 regions. Amplification patterns indicated that MF-MR primers amplified both Apis mellifera and Apis dorsata subsp. binghami, whereas CF-CR primers amplified Apis cerana and Apis nigrocincta. This cross-amplification among closely related Apis species indicates partial primer specificity rather than absolute species exclusivity. Sequence analysis confirmed high similarity to reference sequences, with BLAST-N identities of 99.58% (A. mellifera), 99.29% (A. cerana), 99.67% (A. dorsata subsp. binghami), and 91.25% (A. nigrocincta). Phylogenetic reconstruction revealed distinct clustering of samples with their respective reference taxa, supporting reliable species-level discrimination when PCR results are combined with sequencing and phylogenetic inference. These findings demonstrate that the mrjp2 gene is a robust molecular marker for authenticating the entomological origin of honey in Indonesia. While primer-based PCR provides an initial indication of bee species origin, definitive authentication relies on sequence analysis and phylogenetic validation rather than PCR amplification alone.